The maid's diary : a novel - White, Loreth Anne (Montlake, 2023)
Kit Darling is a maid with a snooping problem. She's the 'invisible girl,' compelled to poke into her wealthy clients' closely guarded lives. It's a harmless hobby until Kit sees something she can't unsee in the home of her brand-new clients, a secret so dark it could destroy the privileged couple expecting their first child. This makes Kit dangerous to the couple. In turn, it makes the couple, who might kill to keep their secret, dangerous to Kit. When homicide cop Mallory Van Alst is called to a scene at a luxury waterfront home known as the Glass House, she's confronted with evidence of a violent attack so bloody it's improbable the victim is alive. But there's no body. The homeowners are gone. And their maid is missing. The only witness is the elderly woman next door, who woke to screams in the night. The neighbor was also the last person to see Kit Darling alive. As Mal begins to uncover the secret that has sent the lives of everyone involved on a devious and inescapable collision course, she realizes that nothing is quite as it seems. And no one escapes their past.